(untitled) (BIBECHANA, 2026)
We study the static Coulomb stress change (ΔCFS) produced by 2015 Gorkha earthquake using a rectangular fault model and the Okada (1992) elastic dislocation solution in a homogeneous, isotropic half-space. We tested five slip scenarios (S1–S5: 2.0–6.5 m) with a shear modulus of 30 × 10⁹ Pa and friction coefficient of 0.4. Stress fields were first computed along 1D profiles extending ±200 km from the rupture center and subsequently used to construct 2D stress maps. The results show that peak ΔCFS increases linearly with slip amplitude, with the highest-slip case (6.5 m) producing 13 MPa at the epicenter. Regression analysis confirms a strong linear scaling (ΔCFS ≈ 2.13 × Slip, R² ≈ 0.92), indicating that each meter of slip enhances peak stress by 2.13 MPa. The 2D stress maps reveal symmetric positive and negative lobes around the rupture, with stress decaying rapidly with distance. The longitudinal stress profiles along longitudinal demonstrate a sharp concentration of stress at the epicenter (28.147°N, 84.708°E) with symmetric decay to zero levels within about ±1.3° longitude. These findings indicate that slip amplitude primarily governs local stress concentration with short-range triggering potential, while far-field stress patterns are comparatively insensitive to variations in slip magnitude.